PENGARUH KREDIT INVESTASI PERBANKAN TERHADAP PERKEMBANGAN SEKTOR EKONOMI DI PROVINSI KALIMANTAN BARAT - B01106045, Indra Sastrawan (Jurnal Pembangunan dan Pemerataan, 2013)
This study entitled "The Effect of Investment Banking Credit Toward Economic Sector Development in West Kalimantan". The problem of this study is whether the investment lending banks affects the development of the economic sector in West Kalimantan which aims to determine the factors that affect the agricultural sector investment loans, the mining sector, the industrial sector, the trade, the service sector, the construction sector and the transport sector to development of the economic sector in West Kalimantan and to find out which banks have a greater influence on the development of economic sectors in West Kalimantan. The author uses descriptive method used to see the effect or the relationship between the independent variables (agriculture, mining, industrial sector, trade, services sector, construction, transport) to the dependent variable (GDP). The model used in this study is the panel regression model. Based on the results of research conducted by the authors, it can be concluded that the government's bank significantly influence the development of the economy (GDP) in West Kalimantan, while private banks had no significant effect. It was caused by the influence of government banks known to the public than private banks. So people do more investment credit banks. Key word: Credit, Investment Banking, Economic Sector